Development of self-breathing polymer electrolyte membrane fuel cell stack with cylindrical cells. (1st July 2022) - Sapkota, Prabal; Brockbank, Paul; Aguey-Zinsou, Kondo-Francois
Abstract: Self-breathing fuel cells use oxygen directly from the atmosphere and this eliminates the need of air fans and humidifiers, and as such enables applications where a reduction in size and volume of the power systems is important. Herein, we report a novel design and fabrication of a 12 celled cylindrical self-breathing stack made from stainless steel. A cylindrical geometry was implemented to permit higher self-breathing function and means to improve the Membrane Electrode Assembly compaction and thus reduce hydrogen leaks. The stack delivered a maximum voltage of 9.4 V and a maximum power of 1 W cm −2 while operating under ambient condition (25 °C, 20% relative humidity and with dry hydrogen). The stainless steel bipolar plates provided enough compaction to the stack to minimize ohmic resistance and the hydrogen sealing was done with silicon gaskets which facilitated the stacking of the cells. The developed 12 celled stack delivered a volume power density of 29 W per litre which is 80% higher than previously reported self-breathing polymer electrolyte membrane fuel cells. Graphical abstract: Image 1 Highlights: A cylindrical self-breathing PEMFC stack was designed to deliver 2 W and 10 V. A low ohmic resistance was achieved by using stainless steel bipolar plates. The stack delivered a maximum power density of 1 W cm −2 at 4.2 V. Self-breathing and self-humidification was verified at 170 mA cm −2 and 5.4 V.